A Feminist Discourse on the Global Indian Surrogacy Bazaar - Saravanan, Sheela (feminists@law, 2018)
The transnational Indian surrogacy markets are a classic case of how rampant violations of human and child rights, women’s bodily integrity and medical ethics thrive on global structural inequalities. In the garb of reproductive liberty, the surrogacy practice promotes deeply embedded pronatalist, patriarchal, racial and ableist hegemony. This raises globally relevant questions of geneticisation, alienation of the gestational role, human and child rights violations, trafficking and reproductive injustice. In her book, The Sexual Contract, Carole Pateman critiques the fact that patriarchal control prevails in the marriage contract, the prostitution contract, and the contract for surrogate motherhood. My research, recently also published as a book titled A Transnational Feminist View of Surrogacy Biomarkets in India, shows the link between the three kinds of sexual contracts elaborated in Carole Pateman’s book. India banned surrogacy on reported deaths of surrogate mothers and egg donors, custody battles for children, abandonment of disabled and undesired children and exploitation of women, apart from trafficking for surrogacy. The illegal chain of networks trafficking young girls from poor localities in India for prostitution and domestic work has also been used for surrogacy. The surrogacy practice maintains patriarchy through familial persuasion and contracts that control and exploit women’s bodies and effect triple-alienation: from the children born, from their own body and physical alienation. Applying the reproductive justice framework, I argue that surrogacy is likely to put the surrogate mother through multiple forms of indignity and injustice along with life risk and hence cannot be considered the intended parent’s reproductive right.